An introduction to early childhood special education (Boston : Allyn and Bacon, 1997)
This book is about: Early intervention services for infants, toddlers, and preschoolers; Typical stages of early childhood development; Special education services; ...
Keywords: Education; Handicapped children; Handicapped children -- Education (Early childhood) -- United States; Handicapped children -- Services for -- United States; Handicapped children -- United States -- Development; Special education -- Activity programs -- United States